Association Between Weight and Height of Children and Eruption of Permanent Teeth in Mosul City Center-Iraq - Ghada Dh Al-Sayagh; Aisha A Qasim; Karam H Jazrawi (University of Mosul, College of Dentistry, 2013)
Aims: To evaluate the effect of length and weight of 5-13 years old children on eruption of permanent teeth in Mosul City. Materials and Methods: The sample consisted of 894 children and teenagers; 412 males and 482 females ranging in age from 5-13 years. A tooth was defined as erupted when any part of its crown pierced its gingiva. The sample was divided into 4 age groups: Group 1: 250 child and teenager aged 5-